A NORMATIVE MODEL FOR ASSESSING COMPETITIVE STRATEGY - Ungerer, Gerard David; Cayzer, Steve (The South African Journal of Industrial Engineering, 2016)
The hyper-competitive nature of e-business has raised the need for a generic way to appraise the merit of a developed business strategy. Although progress has been made in the domain of strategy evaluation, the established literature differs over the ‘tests’ that a strategy must pass to be considered well-constructed. This paper therefore investigates the existing strategy-evaluation literature to propose a more integrated and comprehensive normative strategic assessment that can be used to evaluate and refine a business’ s competitive strategy , adding to its robustness and survivability.